Using Non-Fourier’s Heat Flux and Non-Fick’s Mass Flux Theory in the Radiative and Chemically Reactive Flow of Powell–Eyring Fluid - Hina Firdous (MDPI AG, 2021)
The behavior of convective boundary conditions is studied to delineate their role in heat and mass relegation in the presence of radiation, chemical reaction, and hydro-magnetic forces in three-dimensional Powell–Eyring nanofluids. Implications concerning non-Fourier’s heat flux and non-Fick’s mass flux with respect to temperature nanoparticle concentration were examined to discuss the graphical attributes of the principal parameters. An efficient optimal homotopy analysis method is used to solve the transformed partial differential equations. Tables and graphs are physically interpreted for significant parameters.